Kecerdasan Spiritual dengan Kepuasan Kerja Guru Tahfiz Al-Haramain - Roswandi, Edy; Sani, Abdul; Komalasari, Shanty (Jurnal Al-Husna, 2020)
Speaking of teachers, in the present with high urban living needs, if only looking at how the type of work is also at the same time obtaining job satisfaction then most people will choose jobs with more income and leave lower income. Aims to determine the relationship of spiritual intelligence with job satisfaction teacher Tahfiz Alharamain Banjarmasin. The hypothesis proposed in this study is that there is a significant positive relationship between spiritual intelligence and job satisfaction. This research is quantitative with Purposive Sample sampling technique. This research data collection instrument uses a Likert scale model and data analysis uses Product Moment correlation with the help of SPSS. The results of this study indicate that the calculated r value (0.710)> r table (sig 5% = 0.404) (p value <0.05). Then the hypothesis which states that there is a "Relationship between spiritual intelligence and job satisfaction of teachers of Al-Haramian tahfiz Banjarmasin.